An approach to assessing the implementation of the results of scientific and technical activities within the framework of the smart city digital platform - B. N. Panshin; D. A. Serebryakov (Цифровая трансформация)
In the article, we consider state digital platforms as mechanisms for the practical implementation of the results of scientific research. The need for closer integration of digital platforms and the existing R&D infrastructure is justified by increasing the efficiency of Belarusian science. Currently, innovations aimed at developing human potential and increasing the economic return from its use are very relevant. We want to achieve the maximum number of such innovations. A unified approach to assessing the dynamics of human potential through the introduction of R&D results is proposed. The unified approach is applied in the typical concept for the development of «Smart Cities» in the Republic of Belarus (2019). The necessity of forming a regional network of intersectoral laboratories and a data bank of standard projects for the digitalization of urban space is substantiated.